Over Restriction of Dietary Protein Allowance: The Importance of Ongoing Reassessment of Natural Protein Tolerance in Phenylketonuria - Pinto, Alex (2020)
Phenylalanine (Phe) tolerance is highly variable in phenylketonuria (PKU) and rarely described in patients aged ≥12 years. Patients ≥12 years of age with PKU were systematically challenged with additional natural protein (NP) if blood Phe levels remained below 480 µmol/L (i.e., upper target blood Phe level for patients aged ≥12 years using Portuguese PKU guidelines). In PKU patients, NP tolerance was calculated at baseline and a median of 6 months after systematic challenge with NP whilst patients were maintaining a blood Phe ≤480 μmol/L. Anthropometry was assessed at both times. Routine blood Phe levels were collected. We studied 40 well-controlled PKU patients (10 hyperphenylalaninemia (HPA), 23 mild and 7 classic PKU), on a low-Phe diet with a mean age of 17 years (12-29 years). Median daily NP intake significantly increased between assessments (35 vs. 40 g/day, p = 0.01). Twenty-six patients (65%) were able to increase their median NP intake by a median 12 g/day (2-42 g)/day and still maintain blood Phe within target range. Out of the previous 26 patients, 20 (77%) (8 HPA, 11 mild and 1 classical PKU) increased NP from animal sources (e.g. dairy products, fish and meat) and 6 patients (23%) (3 mild and 3 classical PKU) from plant foods (bread, pasta, potatoes). Median protein equivalent intake from Phe-free/low-Phe protein substitute decreased (0.82 vs. 0.75 g/kg, p = 0.01), while median blood Phe levels remained unchanged (279 vs. 288 μmol/L, p = 0.06). Almost two-thirds of patients with PKU tolerated additional NP when challenged and still maintained blood Phe within the national target range. This suggests that some patients with PKU treated by a low-Phe diet only may over restrict their NP intake. In order to minimise the burden of treatment and optimise NP intake, it is important to challenge with additional NP at periodic intervals.